The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00438-011-0612-5
|View full text |Cite
|
Sign up to set email alerts
|

EMSY overexpression disrupts the BRCA2/RAD51 pathway in the DNA-damage response: implications for chromosomal instability/recombination syndromes as checkpoint diseases

Abstract: EMSY links the BRCA2 pathway to sporadic breast/ovarian cancer. It encodes a nuclear protein that binds to the BRCA2 N-terminal domain implicated in chromatin/transcription regulation, but when sporadically amplified/overexpressed, increased EMSY level represses BRCA2 transactivation potential and induces chromosomal instability, mimicking the activity of BRCA2 mutations in the development of hereditary breast/ovarian cancer. In addition to chromatin/transcription regulation, EMSY may also play a role in the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 78 publications
1
40
0
Order By: Relevance
“…The EMSY locus is amplified in sporadic breast cancer (13%) and higher-grade ovarian cancer (17%). At the cellular level, EMSY overexpression leads to defective HR (Cousineau & Belmaaza 2011), consistent with the notion that the EMSY-binding region of BRCA2 is likely to coincide or overlap with the PALB2-interacting region.…”
Section: Palb2supporting
confidence: 80%
See 1 more Smart Citation
“…The EMSY locus is amplified in sporadic breast cancer (13%) and higher-grade ovarian cancer (17%). At the cellular level, EMSY overexpression leads to defective HR (Cousineau & Belmaaza 2011), consistent with the notion that the EMSY-binding region of BRCA2 is likely to coincide or overlap with the PALB2-interacting region.…”
Section: Palb2supporting
confidence: 80%
“…This region of BRCA2 was also reported to bind to EMSY (HughesDavies et al 2003). The EMSY-binding region of BRCA2 is encoded by exon 3, which is known to be deleted in cancer (Hughes-Davies et al 2003, Cousineau & Belmaaza 2011. The EMSY locus is amplified in sporadic breast cancer (13%) and higher-grade ovarian cancer (17%).…”
Section: Palb2mentioning
confidence: 99%
“…Multiple studies have confirmed the functional link between BRCA2 and EMSY [5][6][7]. EMSY was found to inactivate the function of BRCA2, leading to the development of sporadic breast and ovarian cancers [8,9].…”
Section: Introductionmentioning
confidence: 94%
“…It binds BRCA2, but not BRCA1, through the EMSY N-terminal (ENT) domain. Although the function of EMSY has not been extensively investigated, existing evidence suggests that it may contribute to chromatin modification, DNA repair, and transcription (10,11). EMSY was found to colocalize with BRCA2 on dsDNA breaks.…”
mentioning
confidence: 99%